PERSEPSI ANGGOTA TENTANG PEMBAGIAN SISA HASIL USAHA (SHU) PADA KOPERASI MULTI FINANCEDI KOTA PONTIANAK - Meulan, Meulan; Parijo, Parijo; Buwono, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCooperative is a business entity consisting of persons-a legal entity or legal entity based on its activities based on the principle of cooperatives as well as a people's economic movement based on the principle of kinship. Cooperatives as a populist economic movement in its activities do not recognize the term profit because the business activities of the main cooperative is not oriented to profit (non profitoriented) but rather beneficial oriented (member) to the members.Research method in this research is descriptive method with form of case study. The data source in this research is Cooperative Members. This study uses data collection techniques, direct observation with data collection tools in the form of Observation Guide, Interview Guidelines, and Field Disability. The results of the study conclude that the distribution of the remaining results of operations for members, in this case there are differences, of some members tend to disagree.Distribution of the remaining results of operations for the board, in this case the members tend to disagree disagree. Distribution of the remaining results of operations for the regulatory body, in this case the members of the perceive not agree.So it can be concluded that the distribution of the remaining results of operations on Cooperative Multi Finance according to the perception of members and supported by the Study Library in the category of not agreeing. Keywords:  Cooperative, Perception, Shu Division